Detachment of the Klaipėda Region from Lithuania in 1939 – a catalyst for the Second World War? - Vyšniauskas, Arūnas (Genocidas ir rezistencija, 2025)
In the complex sequence of events, historians often refer to the fact of the enforced detachment of the Klaipėda region from Lithuania and its annexation to Germany in March 1939, without dwelling on it too much, focusing more on the Austrian Anschluss of 1938, the Munich Conference of 1938, and the destruction of Czechoslovakia, with its fateful moments in mid-March 1939. The Klaipėda case, however, is particularly worth mentioning because it represented the last territorial expansion of the German Reich before the war, and it took place without a direct military confrontation, as Lithuania acquiesced to an ultimatum from Berlin. The German invasion of Poland on 1 September 1939, which turned into a world war, overshadowed the extraordinary significance of the annexation of the Klaipėda region to the Reich on 22 and 23 March 1939 in the chain of fateful pre-war events. Here, foreign historians focus on the escalating tensions between Germany and Poland over the German ferry Danzig and the demands for an extraterritorial corridor to East Prussia, the political approximation between Germany and the Soviet Union that led to the so-called Molotov-Ribbentrop Pact, etc. By using the term catalyst in the title of this article, and by arguing figuratively for the use of this resonant word in the article itself, we aim to underline the extraordinary international significance of the Klaipėda (Memel) issue for the further acceleration of the course of events.This had far-reaching implications for the wider international scene of the time. An  examination of the media and other historical sources from the Western democracies in 1939 reveals that the NS Germany’s harsh ultimatum solution to the Klaipėda problem and its threat to use its military forces against a small neighbouring country for an invasion deep into Lithuania accelerated the preparations of other European states for the inevitable armed conflicts and played an important role in the shaping of the fate of the whole geopolitical area between Germany and the USSR. Ultimately, it contributed to the subsequent agreements on the division of spheres of influence between the two totalitarian powers.
Keywords: Klaipėda region; genesis of the Second World War; the Baltic states; Germany; Poland; USSR; Great Britain; 1939